Formulation development and investigation of domperidone transdermal patches - Prabhu, Prabhakar; Shah, Samip; Gundad, Shankar (International Journal of Pharmaceutical Investigation)
Aim and Background: Domperidone is a dopamine antagonist with antiemetic properties having a plasma half life of 7-9 h with 15% oral bioavailability. In the present work transdermal patches of domperidone were prepared with the objective to improve its therapeutic efficacy, patient compliance and to reduce the frequency of dosing and side effects, as well as to avoid its extensive first pass metabolism of the drug. Materials and Methods: The patches were prepared using ethyl cellulose (EC): Poly vinyl pyrrolidone (PVP), poly vinyl alcohol (PVA): Poly vinyl pyrrolidone (PVP) and hydroxypropylmethylcellulose (HPMC): Sodium (carboxy methyl cellulose) CMC as polymers in combination. The physicochemical parameters like thickness, drug content, weight variation, moisture absorption and drug permeation studies were evaluated for the prepared patches. No significant difference in thickness, average weight and in the drug content among the patches. Results: It was observed that from hydrophilic polymers the drug release was found to be faster compared to (F5 and F6 & F3 and F4) combination of hydrophilic and lipophilic polymers used in the study. Patches containing HPMC and Sodium CMC (F5 and F6) showed faster release as the patches showed maximum percentage amount moisture absorption. The in vitro release data was treated with kinetic equations and it followed Higuchi's diffusion mechanism. The in vivo bioavailability study was performed in rats and observed that, drug reached to the peak in approximately 60 min (16%) after oral route of administration. However, approximately same amount of drug was found in the serum from transdermal formulation in 6 h and further increase in the amount of drug in the serum, indicated that the drug 5 bioavailability could be better and hence the hepatic metabolism can be avoided, as it is evident from the data. Further, the decrease in the amount of drug present in the serum 45 min after oral administration also indicated that major amount of drug might have got metabolized and the bioavailability is reduced. However, the transdermal patch released further amount of drug (33%) at the end of 24 h. Conclusion: The present study can be concluded that transdermal patch can extend the release of drug for many hours with better bioavailability and also can avoid the first pass effect.
Keywords: Domperidone; in vitro and in vivo release study; transdermal patch